Foot Massage dan Joint Mobility Exercises terhadap Nilai Ankle Brachial Index (ABI) pada Pasien DM Tipe 2 - Isni Hijriana; Miniharianti Miniharianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of foot massage and joint mobility exercises on the value of ABI in type 2 DM patients. The quantitative research used a quasi-experimental approach with pre-test and post-test designs with two intervention groups. The results showed that the Wilcoxon signed ranks test statistic on 20 respondents in the two intervention groups showed a difference after being given foot massage and joint mobility exercises intervention on the ABI value, with each p-value (p = 0.00). In conclusion, foot massage and joint mobility exercises effectively improve peripheral circulation and increase ABI values in Type 2 DM patients. Keywords: Ankle Brachial Index (ABI), Type 2 DM, Foot Massage, Joint Mobility Exercises